Comparative assessment of profile storage of soil organic carbon and total nitrogen in forest and grassland in Jajarkot, Nepal - Sharma, Mamata; Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2020)
Understanding distribution of soil organic carbon and nitrogen in soil profile is important for assessing soil fertility and soil carbon dynamics. However, little is known about their distribution in soil depth below 30cm in Nepal. In this context, this research was carried out in 2019 to determine the Soil Organic Carbon (SOC) and Total Nitrogen (TN) in 0-10 cm, 11-30 cm and 31-60 cm depths of soil profile at forest and grassland in Kotila community forest, Jajarkot, Nepal. Overall field measurement was based on national standard protocols. Three replicates of soil pit from forest and grassland were dug for soil sample collection. Approximately 100 g soil sample from each soil layer was collected and taken to laboratory for SOC analysis. Separate soil samples, one sample from each soil layer were collected with the help of a metal soil corer having volume 245.22cm3 to quantify bulk density. Forest has 25.42 ton/ha SOC stock and 3.28 ton/ha TN stock up to 60 cm soil depth. Likewise, Grassland has 21.19 ton/ha SOC stock and 3.14 ton/ha TN stock up to 60cm soil depth. However, these values are not significantly different at 5 % level of significance. The SOC and TN were decreased with increased soil depths, though not significantly different at 5 % level of significance. The C:N ratio was found higher in forest than grassland. It is concluded that SOC and TN do not vary significantly between forest and grassland. Topsoil contains more SOC, TN, and C:N ratio, so the management practices should focus on maintaining inputs of soil organic matter in the forest and grassland.